A study of the impact of plunging waves on the inverted L-shaped breakwater structure based on SPH method - Ma, Z. (Taylor and Francis Ltd., 2021)
An obvious slamming phenomenon appears at the inverted âL-shapedâ breakwater when impinged by waves. Based on the DualSPHysics numerical program, a numerical tank which can simulate plunging waves is established. The single-phase flow model is adopted in this program, GPU parallel acceleration processing framework and dynamic boundary particles (DBPs) are implemented to improve the calculation efficiency and accuracy. Additionally, The article analyses the characteristics of the slamming pressure amplitude and the spatial distribution of the three structures (Str.0, Str.1and Str.2), and the water particles of the flow condition of the wave field near the structure and velocity distribution are also studied. It is found that the slamming pressure peaks on Str.1 and Str.2 are both reduced by more than 40 percent compared to that on Str.0. Meanwhile, the slamming pressures near the upper corner on Str.1 and Str.2 reduce significantly. Therefore, the optimisation of the structural chamfer is beneficial to effectively improving the safety and stability of the structure. Â© 2021 Informa UK Limited, trading as Taylor & Francis Group.